Child and adolescent mental health services in Pakistan: current situation, future directions and possible solutions - Khan, Faria (Int Psychiatry, 2008)
Worldwide, mental disorders are on the increase (Gadit, 2007) and an estimated 10–20% of children have one or more mental or behavioural problems (Park, 2002). There is an urgent and serious need to pay attention to the mental health needs of children in low- and middle-income countries (Rahman et al, 2000). The initial survey for the World Health Organization’s Atlas project (Sherer, 2002) showed that 41% of countries surveyed had no mental health policy and 28% had no separate budget for mental health.